Interpretation of treaties: to the discussion of nature, concepts and functions - Карвацька, Світлана Богданівна (Pan-European University Faculty of Law Tomášikova, 10 Bratislava; Uzhhorod National University Faculty of Law Kapituľna, 26 Uzhhorod; Public organization „LEX PRO OMNES” Mierová, 2529 Humenné; Public organization „Association of International Educational аnd Scientific Cooperation” Kapituľna, 26 Uzhhorod, 2021)
The article explores the main problematic issues of treaty interpretation: nature, concepts, and functions. It has been proved that treaty interpretation is a process carried out in international litigation, the purpose of which is to establish the true content of a treaty via defining its normative essence by giving due meaning to contradictory terms (provisions) to be used in international disputes, provided by the VCLT or developed by judicial practice. Treaty interpretation is not a political or legislative process. The rules of interpretation, defined by the VCLT, remain relevant today; however, they require interpretation that would correspond to modern realities.
Keywords: international law, Vienna Convention on the Law of Treaties, subsequent agreements, rules of interpretation, judicial practice